Atezolizumab With Neoadjuvant Anti–Human Epidermal Growth Factor Receptor 2 Therapy and Chemotherapy in Human Epidermal Growth Factor Receptor 2–Positive Early Breast Cancer: Primary Results of the Randomized Phase III IMpassion050 Trial. Issue 25 (1st September 2022) - Huober, Jens; Barrios, Carlos H.; Niikura, Naoki; Jarząb, Michał; Chang, Yuan-Ching; Huggins-Puhalla, Shannon L.; Pedrini, José; Zhukova, Lyudmila; Graupner, Vilma; Eiger, Daniel; Henschel, Volkmar; Gochitashvili, Nino; et al.
Abstract : PURPOSE: Combining standard of care (pertuzumab-trastuzumab [PH], chemotherapy) with cancer immunotherapy may potentiate antitumor immunity, cytotoxic activity, and patient outcomes in high-risk, human epidermal growth factor receptor 2 (HER2)–positive early breast cancer. We report the phase III IMpassion050 primary analysis of neoadjuvant atezolizumab, PH, and chemotherapy in these patients. METHODS: Patients with a primary tumor of > 2 cm and histologically confirmed, positive lymph node status (T2-4, N1-3, M0) were randomly assigned 1:1 to atezolizumab/placebo with dose-dense doxorubicin/cyclophosphamide, followed by paclitaxel, and PH. After surgery, patients were to continue atezolizumab/placebo and PH (total: 1 year of HER2-targeted therapy); those with residual disease could switch to ado-trastuzumab emtansine with atezolizumab/placebo. Coprimary efficacy end points were pathologic complete response (pCR; ypT0/is ypN0) rates in intention-to-treat (ITT) and programmed cell death-ligand 1 (PD-L1)–positive populations. RESULTS: At clinical cutoff (February 5, 2021), pCR rates in the placebo and atezolizumab groups in the ITT populations were 62.7% (n = 143/228) and 62.4% (n = 141/226), respectively (difference –0.33%; 95% CI, –9.2 to 8.6; P = .9551). The pCR rates in the placebo and atezolizumab groups in patients with PD-L1–positive tumors were 72.5% (n = 79/109) and 64.2% (n = 70/109), respectively (difference –8.26%; 95% CI, –20.6 to 4.0; P = .1846). Grade 3-4 and serious adverse events were more frequent in the atezolizumab versus placebo group. Five grade 5 adverse events occurred (four neoadjuvant, one adjuvant; two assigned to study treatment), all with atezolizumab. Overall, the safety profile was consistent with that of atezolizumab in other combination studies. CONCLUSION: Atezolizumab with neoadjuvant dose-dense doxorubicin/cyclophosphamide–paclitaxel and PH for high-risk, HER2-positive early breast cancer did not increase pCR rates versus placebo in the ITT or PD-L1–positive populations. PH and chemotherapy remains standard of care; longer follow-up may help to inform the long-term impact of atezolizumab.